2021
DOI: 10.3390/children8060515
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Temporomandibular Joint Range of Motion and Related Factors in Children and Adolescents

Abstract: This study was designed to establish safe guidelines for pediatric dental practice regarding temporomandibular joint (TMJ) range of motion (ROM) and mouth area (MA). A total of 438 children aged 3–15 years old of homogenous ethnicity participated in the study; the distribution of participants was approximately equal (sex; n = 15; age, n = 30). Maximum mouth opening (MMO), body height, weight, and age of each participant were recorded, and the TMJ ROM including anterior and lateral movements, MA, and mouth widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 16 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…When comparing men and women, they found significant differences in the mouth opening, being greater in men. Park et al [ 18 ] conducted a similar study in children, obtaining similar results. Singh et al [ 19 ] studied the mandibular opening in 756 adults in Yamunanagar City, Haryana, India, and found that the men had a greater mandibular opening (45.36 ± 6.70 mm) than the women (41.27 ± 6.75 mm) with a significant p -value ( p = 0.000).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…When comparing men and women, they found significant differences in the mouth opening, being greater in men. Park et al [ 18 ] conducted a similar study in children, obtaining similar results. Singh et al [ 19 ] studied the mandibular opening in 756 adults in Yamunanagar City, Haryana, India, and found that the men had a greater mandibular opening (45.36 ± 6.70 mm) than the women (41.27 ± 6.75 mm) with a significant p -value ( p = 0.000).…”
Section: Discussionmentioning
confidence: 61%
“…Several studies use the definition of distance between edges of front incisors not including overbite [ 5 , 19 , 20 , 40 , 41 ], or including overbite [ 22 , 23 ]. Others consider the vertical distance between edges of frontal incisors [ 18 ], vertical dimension [ 31 ] or distances between edges of canines [ 30 ]. The use of mouth opening angle like an alternative to assess mouth opening has led to developing measurement instruments [ 7 , 24 , 27 , 28 ] or techniques to estimate it [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Since children cannot truly describe their discomfort and pain, localize their painful symptoms, or understand questions related to their pain, TMJa can easily go undiagnosed. 10 Thus, early diagnosis and treatment of TMJ ankylosis in children (TMJa) are crucial for both functional and aesthetic outcomes. 16 Limited MO measurements are the clinical manifestations of children with TMJa.…”
Section: Di̇scuss I Onmentioning
confidence: 99%
“…9 There are many different devices and techniques for MMO measurements in the literature. 9,10,[17][18][19] In these studies, this parameter has been used for different landmarks, such as the distance between the upper-lower incisor, the distance of the alveolar crest, and the most excellent vertical mandibular opening. Moreover, predicting post-op facial profiles is a crucial aspect of surgical procedures.…”
Section: Di̇scuss I Onmentioning
confidence: 99%